ПАРАМЕТРЫ ЗАТОЧКИ МОНОМЕТАЛЛИЧЕСКОГО ЛЕЗВИЯ ПОЧВООБРАБАТЫВАЮЩИХ ОРГАНОВ С ЦЕЛЬЮ ОБЕСПЕЧЕНИЯ ОСТРИЯ В НАПРАВЛЕНИИ РЕЗАНИЯ ПОЧВЫ - Шамшетов Сарсенбай Нуратдинович; Авезова Зияда Кидирбаевна (Galaxy International Interdisciplinary Research Journal, 2022)
In article it analyses process of the influence of ground on surface, worker organ cotton cultivator. Recommendations are given on sharpening blade worker organ cultivator, reducing pressures of ground on them.